Mapping of research on maternal health interventions in low- and middle-income countries: a review of 2292 publications between 2000 and 2012. Issue 1 (December 2016) - Chersich, Matthew; Blaauw, Duane; Dumbaugh, Mari; Penn-Kekana, Loveday; Thwala, Siphiwe; Bijlmakers, Leon; Vargas, Emily; Kern, Elinor; Kavanagh, Josephine; Dhana, Ashar; Becerra-Posada, Francisco; Mlotshwa, Langelihle; et al.
Abstract Background Progress in achieving maternal health goals and the rates of reductions in deaths from individual conditions have varied over time and across countries. Assessing whether research priorities in maternal health align with the main causes of mortality, and those factors responsible for inequitable health outcomes, such as health system performance, may help direct future research. The study thus investigated whether the research done in low- and middle-income countries (LMICs) matched the principal causes of maternal deaths in these settings.  Methods Systematic mapping was done of maternal health interventional research in LMICs from 2000 to 2012. Articles were included on health systems strengthening, health promotion; and on five tracer conditions (haemorrhage, hypertension, malaria, HIV and other sexually transmitted infections (STIs)). Following review of 35, 078 titles and abstracts in duplicate, data were extracted from 2292 full-text publications. Results Over time, the number of publications rose several-fold, especially in 2004–2007, and the range of methods used broadened considerably. More than half the studies were done in sub-Saharan Africa (55.4 %), mostly addressing HIV and malaria. This region had low numbers of publications per hypertension and haemorrhage deaths, though South Asia had even fewer. The proportion of studies set in East Asia Pacific dropped steadily over the period, and in Latin America from 2008 to 2012. By 2008–2012, 39.1 % of articles included health systems components and 30.2 % health promotion. Only 5.4 % of studies assessed maternal STI interventions, diminishing with time. More than a third of haemorrhage research included health systems or health promotion components, double that of HIV research. Conclusion Several mismatches were noted between research publications, and the burden and causes of maternal deaths. This is especially true for South Asia; haemorrhage and hypertension in sub-Saharan Africa; and for STIs worldwide. The large rise in research outputs and range of methods employed indicates a major expansion in the number of researchers and their skills. This bodes well for maternal health if variations in research priorities across settings and topics are corrected.